Transition metal doped copper micron wire catalyst and preparation method and biomass reduction application thereof
By preparing the transition metal doped copper micron catalyst, the problem of high catalyst costs in the existing electrocatalyst hydrogenation method has been solved, and high -efficiency, selective and stable catalytic effects have been achieved, and they have good industrial application prospects.
Patent Information
- Application Number
- CN202411528493.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-24
AI Technical Summary
The catalysts used in existing electrocatalytic hydrogenation methods are costly and have poor stability, making it difficult to meet the needs of large-scale applications.
The transition metal doped copper micron catalyst is prepared through steps such as ion corrosion, annealing, electrochemical reduction, and transition metal doping to improve the surface area and activity site of the catalyst, and enhance their stability and catalytic performance.
It achieves catalytic effects of high conversion rate, high selectivity and high stability, reduces the preparation cost of the catalyst, and has good industrial application prospects.
Smart Images

Figure CN119352089A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomass catalysis, and in particular to a transition metal-doped copper microwire catalyst, a preparation method thereof, and biomass reduction application. Background Art
[0002] Biomass, as an important renewable resource, is a green alternative to traditional non-renewable fossil energy. By converting biomass into platform molecules, a series of high-value fuels or chemicals traditionally derived from fossil resources can be further obtained. For example, the selective hydrogenation of the biomass-based platform compound 5-hydroxymethylfurfural (HMF) can produce 2,5-furan dimethanol (BHMF), which is an important high-value diol used in fine chemical synthesis, preparation of new functionalized polyethers, polyurethanes and their pharmaceutical polyheterocyclic compounds.
[0003] In recent years, electrocatalytic furanaldehyde conversion technology has received great attention. The electrocatalytic hydrogenation method is similar to the traditional thermal catalytic hydrogenation. The key difference is that the active hydrogen involved in the reaction is generated in situ on the electrode surface by protons or water, and does not involve the dissociation of hydrogen. Therefore, this method does not require high temperature, high pressure hydrogen atmosphere and expensive hydrogenation reagents. The reaction conditions are mild and the process is easy to control. However, the large-scale use of electrocatalytic hydrogenation needs to rely on catalytic materials with good catalytic properties. The catalysts used in the current electrocatalytic hydrogenation method often involve precious metal modification, and the preparation and application costs of the catalysts are high and the stability is poor. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to develop a low-cost catalyst with high conversion rate, high selectivity and high stability for the electrocatalytic hydrogenation reaction of furan aldehyde organic small molecules.
[0005] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a transition metal-doped copper microwire catalyst, comprising the following steps: S1. Prepare copper matrix material, clean and dry it for later use; S2, immersing the pretreated copper substrate material in a mixed solution of ammonium persulfate and sodium hydroxide for ion corrosion; S3, taking out the material from the mixed solution, washing it and performing a first annealing treatment to obtain a copper oxide micron wire precursor; S4, electrochemically reducing the copper oxide microwire precursor to obtain a copper microwire precursor; S5, immersing the copper microwire precursor in a transition metal solution to perform transition metal doping; S6. Taking out the material from the transition metal solution, performing a second annealing treatment after washing, and cooling to room temperature to obtain a transition metal-doped copper microwire catalyst.
[0006] The present invention processes the copper matrix material through the steps of ion corrosion, annealing, electrochemical reduction, transition metal doping, etc. to obtain a micron-wire structured copper-based catalyst, which has good structural stability and a large specific surface area, improves the adsorption capacity, and the catalyst has high activity.
[0007] Furthermore, in step S2, the concentration of ammonium persulfate in the mixed solution is 0.05-0.5 M, the concentration of sodium hydroxide is 0.5-5 M, and the immersion time of the copper foam is 10-120 min. In this step, the ammonium persulfate, sodium hydroxide and copper matrix material react in situ to generate a micron wire structure, increase the surface area and active sites of the material, and thus improve the catalytic performance.
[0008] Furthermore, in step S3, the first annealing treatment condition is: annealing at 200-350° C. for 0.5-5 h in air or oxygen atmosphere. Annealing can stabilize the microwire structure, remove internal stress, improve structural stability, and enhance the durability of the catalyst.
[0009] Furthermore, in step S4, the electrochemical reduction treatment conditions are: reduction treatment is performed at a constant voltage of -0.1 to -0.5 V vs. RHE in a buffer solution for 0.5 to 5 h; Alternatively, in buffer, -1 to -100 mA cm -2 The reduction treatment was carried out under constant current for 0.5-5 h; Alternatively, cyclic voltammetry was performed in buffer at a cycling potential of 0 to -0.6 V vs. RHE for 10 to 100 cycles.
[0010] Electrochemical reduction treatment can enhance the reduction activity of copper microwires and improve their catalytic performance.
[0011] Furthermore, in step S5, the concentration of the transition metal solution is 0.1-10 mM, and the immersion time of the copper microwire precursor is 1-30 min.
[0012] Furthermore, the transition metal element in the transition metal solution is selected from one or more of cobalt, nickel, iron and manganese.
[0013] In this step, a solution doping method is used to uniformly dope the transition elements on the copper microwires, thereby improving the adsorption capacity of the catalyst for the reaction substrate and greatly enhancing the reaction activity of the catalyst.
[0014] Furthermore, in step S6, the second annealing treatment condition is: annealing in a hydrogen atmosphere at 200-350° C. for 0.5-5 h. The second annealing treatment can further improve the stability and activity of the catalyst.
[0015] The second aspect of the present invention provides a transition metal doped copper microwire catalyst, which is prepared by the above preparation method. The catalyst of the present invention has a uniform microstructure, excellent catalytic performance and stability.
[0016] The third aspect of the present invention provides an application, in which the above-mentioned transition metal-doped copper microwire catalyst is used for electrocatalytic reduction of furan aldehyde organic small molecules to prepare furanol.
[0017] Furthermore, a three-electrode system was constructed, with the transition metal-doped copper microwire catalyst as the working electrode, the concentration of furan aldehyde organic small molecules was 1~1000 mM, and the reaction potential was -0.1~-1 V vs. RHE.
[0018] Furthermore, the furan aldehyde organic small molecule is selected from at least one of furfural, 5-hydroxymethylfurfural, 5-formyl-2-furancarboxylic acid, 2,5-diformylfuran, and 5-hydroxymethyl-2-tetrahydrofuran furfural.
[0019] The transition metal-doped copper microwire catalyst of the present invention has high catalytic activity and selectivity for the electrocatalytic reduction of furan aldehyde organic small molecules, and the preparation method is simple to operate, has strong repeatability, does not use precious metals as raw materials, has low preparation cost, and has good industrial application prospects.
[0020] In summary, compared with the prior art, the present invention has the following beneficial effects: (1) The present invention prepares copper microwires by ion etching technology, thereby increasing the surface area of the material and making the active sites evenly distributed. Then, the solution doping technology is used to efficiently dope transition elements, which significantly improves the substrate adsorption capacity and catalytic performance of the catalyst.
[0021] (2) The present invention eliminates the internal stress of the material through a multi-step annealing treatment, thereby improving the stability of the catalyst, and improves the reduction activity of the catalyst through an electrochemical reduction treatment, thereby enhancing the catalytic performance.
[0022] (3) The present invention is simple to operate and highly reproducible. It can obtain a catalyst with high catalytic activity and selectivity for the electrocatalytic reduction of furan aldehyde-type organic small molecules without using precious metals, and has a good prospect for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a SEM image of the copper microwire precursor in Example 1 of the present invention.
[0024] Figure 2 is a SEM image of the cobalt-doped copper microwire catalyst in Example 1 of the present invention.
[0025] Figure 31 is an element distribution diagram of the cobalt-doped copper microwire catalyst in Example 1 of the present invention.
[0026] Figure 4 It is the LSV curve diagram of the electrochemical workstation in Example 8 of the present invention.
[0027] Figure 5 This is a diagram of the catalytic process of the cobalt-doped copper microwire catalyst in Example 10 of the present invention.
[0028] Figure 6 This is a graph showing the product analysis results of the cobalt-doped copper microwire catalyst at different electrolysis potentials in Example 11 of the present invention. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0030] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0032] A specific embodiment of the present invention provides a nickel-based catalytic material and a preparation method thereof, the preparation method comprising the following steps: S1. Prepare a copper matrix material, clean it with ethanol, hydrochloric acid and deionized water ultrasonically for 5 to 30 minutes, and dry it for use. Pretreatment can remove oxides and impurities on the surface of the copper matrix material, improve the reaction uniformity of subsequent steps, and ensure uniform generation of micrometer lines. In a specific embodiment, the copper matrix material can be in the form of foamed copper, copper sheet, copper foil, etc., preferably foamed copper.
[0033] S2, immersing the pretreated copper matrix material in a mixed solution of ammonium persulfate and sodium hydroxide for ion corrosion. In this step, copper microwires are generated in situ by an ion corrosion method to increase the surface area and active sites of the material. In a specific embodiment, the concentration of ammonium persulfate in the mixed solution is 0.05-0.5 M, the concentration of sodium hydroxide is 0.5-5 M, and the immersion time of the copper matrix material in the mixed solution is 10-60 min.
[0034] S3, taking out the material from the mixed solution, washing it and then performing the first annealing treatment, the annealing conditions are: annealing at 200-350 °C for 0.5-5 h in air or oxygen atmosphere to obtain a copper oxide microwire precursor. Annealing in air or oxygen can stabilize the structure of the copper microwire and remove internal stress.
[0035] S4. Electrochemically reduce the copper oxide microwire precursor to obtain a copper microwire precursor, and further increase its reduction activity. In a specific embodiment, the electrochemical reduction treatment is performed in a buffer solution, and the reduction method can be a constant voltage method (-0.1~-0.5 V vs. RHE constant voltage for 0.5~5 h), a constant current method (-1~-100 mA·cm -2 Reduction treatment is performed under constant current for 0.5-5 h) or cyclic voltammetry (10-100 cycles at a cycling voltage of 0-0.6 V vs. RHE); the buffer may include phosphate buffer (PBS), carbonate buffer (CBS), borate buffer (BBS), sodium sulfate, potassium sulfate, etc.
[0036] S5, immersing the reduced copper microwire precursor in a transition metal solution for transition metal doping. This step uniformly dopes the copper microwire with transition metals to enhance the substrate adsorption capacity and improve the catalytic performance. In a specific embodiment, the concentration of the transition metal solution is 0.1-10 mM, and the immersion time of the copper microwire precursor is 1-10 min; the transition metal element can be cobalt, nickel, iron, manganese, etc.; the transition metal salt form can be chloride, nitrate, sulfate, etc.
[0037] S6. Take out the material from the transition metal solution, perform a second annealing treatment after cleaning, and cool to room temperature. The annealing conditions are: annealing at 200-350 °C in a hydrogen atmosphere for 0.5-5 h to obtain a transition metal-doped copper microwire catalyst.
[0038] The nickel-based catalytic material prepared by the above method is applied to the electrocatalytic reduction of furan aldehyde organic small molecules, which can achieve efficient conversion of furan aldehyde organic small molecules. The specific operation method is: construct a three-electrode system, transition metal-doped copper microwire catalyst as the working electrode, platinum electrode or carbon material electrode as the counter electrode, Hg / HgO reference electrode, saturated calomel electrode or Ag / AgCl reference electrode as the reference electrode; PBS, CBS, BBS, sodium sulfate, potassium sulfate, etc. are selected as the electrolyte; the concentration of furan aldehyde organic small molecules is 1~100 mM, and furan aldehyde organic small molecules include furfural, 5-hydroxymethylfurfural, 5-formyl-2-furancarboxylic acid, 2,5-diformylfuran, 5-hydroxymethyl-2-tetrahydrofuran furfural, etc.; the reaction potential is -0.1~-1 V vs.RHE.
[0039] The technical effects of the present invention are described below in conjunction with specific embodiments. Unless otherwise specified, the raw materials in the embodiments of the present application are purchased through commercial channels.
[0040] Example 1
[0041] 1) Cut the foam copper into 1×2 cm 2 The samples were ultrasonically cleaned with anhydrous ethanol, 1 M hydrochloric acid and deionized water for 10 min each and dried for later use.
[0042] 2) Immerse the cleaned copper foam in a mixed solution of 0.1 M ammonium persulfate and 2 M sodium hydroxide and let it stand at room temperature for 0.5 hour.
[0043] 3) After the reaction is completed, the material is taken out and rinsed with deionized water, and then annealed in air at 250°C for 2 hours to obtain a copper oxide microwire precursor.
[0044] 4) The copper oxide microwire precursor was reduced in 0.5 M PBS solution at -0.4 V vs. RHE for 1 hour to obtain a copper microwire precursor with a large number of microwire structures. Its microscopic morphology is as follows: Figure 1 shown.
[0045] 5) Soak the copper microwire precursor in a 0.5 mM cobalt chloride solution and let it stand at room temperature for 10 minutes.
[0046] 6) Take out the material from the cobalt chloride solution, wash it with deionized water, and dry it in an 80 °C oven for 2 hours. Then, anneal it in a hydrogen atmosphere at 250 °C for 2 hours and cool it to room temperature to obtain a cobalt-doped copper microwire catalyst. The microscopic morphology of the cobalt-doped copper microwire catalyst prepared in this embodiment is as follows: Figure 2 As shown in Figure 1, the overall structure is a micron wire structure with a large surface area. The element distribution of the cobalt-doped copper micron wire catalyst is shown in Figure 1. Figure 3As shown, the cobalt element is evenly distributed in the copper microwires, greatly improving the substrate adsorption and catalytic performance of the catalyst.
[0047] Example 2
[0048] 1) Cut the foam copper into 5×5 cm 2 The samples were ultrasonically cleaned with anhydrous ethanol, 1 M hydrochloric acid and deionized water for 10 min each and dried for later use.
[0049] 2) Immerse the cleaned copper foam in a mixed solution of 0.05 M ammonium persulfate and 2 M sodium hydroxide and let it stand at room temperature for 1 hour.
[0050] 3) After the reaction is completed, the material is taken out and rinsed with deionized water, and then annealed in air at 300°C for 2 hours to obtain a copper oxide microwire precursor.
[0051] 4) The copper oxide microwire precursor was reduced in a 0.5 M PBS solution at -0.4 V vs. RHE for 1 hour to obtain a copper microwire precursor having a large number of microwire structures.
[0052] 5) Soak the copper microwire precursor in a 0.5 mM cobalt chloride solution and let it stand at room temperature for 10 minutes.
[0053] 6) The material was taken out from the cobalt chloride solution, cleaned with deionized water, and dried in an oven at 80°C for 2 hours. Afterwards, it was annealed in a hydrogen atmosphere at 250°C for 2 hours and cooled to room temperature to obtain a cobalt-doped copper microwire catalyst.
[0054] Example 3
[0055] 1) Cut the foam copper into 1×2 cm 2 The samples were ultrasonically cleaned with anhydrous ethanol, 1 M hydrochloric acid and deionized water for 10 min each and dried for later use.
[0056] 2) Immerse the cleaned copper foam in a mixed solution of 0.1 M ammonium persulfate and 2 M sodium hydroxide and let it stand at room temperature for 0.5 hour.
[0057] 3) After the reaction is completed, the material is taken out and rinsed with deionized water, and then annealed in air at 250°C for 2 hours to obtain a copper oxide microwire precursor.
[0058] 4) The copper oxide microwire precursor was reduced in a 0.5 M PBS solution at -0.5 V vs. RHE for 1 hour to obtain a copper microwire precursor having a large number of microwire structures.
[0059] 5) Soak the copper microwire precursor in 1 mM cobalt chloride solution and let it stand at room temperature for 2 minutes.
[0060] 6) The material was taken out from the cobalt chloride solution, cleaned with deionized water, and dried in an oven at 80°C for 2 hours. Afterwards, it was annealed in a hydrogen atmosphere at 250°C for 1 hour and cooled to room temperature to obtain a cobalt-doped copper microwire catalyst.
[0061] Example 4
[0062] 1) Cut the copper sheet into 1×2 cm 2 The samples were ultrasonically cleaned with anhydrous ethanol, 1 M hydrochloric acid and deionized water for 10 min each and dried for later use.
[0063] 2) Immerse the cleaned copper foam in a mixed solution of 0.1 M ammonium persulfate and 2 M sodium hydroxide and let it stand at room temperature for 0.5 hour.
[0064] 3) After the reaction is completed, the material is taken out and rinsed with deionized water, and then annealed in air at 250°C for 2 hours to obtain a copper oxide microwire precursor.
[0065] 4) The copper oxide microwire precursor was reduced in a 0.5 M sodium sulfate solution at -0.4 V vs. RHE for 1 hour to obtain a copper microwire precursor having a large number of microwire structures.
[0066] 5) Soak the copper microwire precursor in a 1 mM cobalt chloride solution and let it stand at room temperature for 5 minutes.
[0067] 6) The material was taken out from the cobalt chloride solution, cleaned with deionized water, and dried in an oven at 80°C for 3 hours. After that, it was annealed in a hydrogen atmosphere at 300°C for 1 hour and cooled to room temperature to obtain a cobalt-doped copper microwire catalyst.
[0068] Example 5
[0069] 1) Cut the copper foil into 2×6 cm 2 The samples were ultrasonically cleaned with anhydrous ethanol, 1 M hydrochloric acid and deionized water for 10 min each and dried for later use.
[0070] 2) Immerse the cleaned copper foam in a mixed solution of 0.1 M ammonium persulfate and 3 M sodium hydroxide and let it stand at room temperature for 0.5 hour.
[0071] 3) After the reaction is completed, the material is taken out and rinsed with deionized water, and then annealed in air at 250°C for 2 hours to obtain a copper oxide microwire precursor.
[0072] 4) The copper oxide microwire precursor was placed in a 0.5 M sodium sulfate solution at -10 mA·cm -2 The reduction treatment was carried out at a current density of for 2 hours to obtain a copper microwire precursor having a large number of microwire structures.
[0073] 5) Soak the copper microwire precursor in 1 mM cobalt nitrate solution and let it stand at room temperature for 10 minutes.
[0074] 6) The material was taken out from the cobalt chloride solution, cleaned with deionized water, and dried in an oven at 80°C for 2 hours. Afterwards, it was annealed in a hydrogen atmosphere at 250°C for 1 hour and cooled to room temperature to obtain a cobalt-doped copper microwire catalyst.
[0075] Example 6
[0076] 1) Cut the foam copper into 10×10 cm 2 The samples were ultrasonically cleaned with anhydrous ethanol, 1 M hydrochloric acid and deionized water for 10 min each and dried for later use.
[0077] 2) Immerse the cleaned copper foam in a mixed solution of 0.1 M ammonium persulfate and 2.5 M sodium hydroxide and let it stand at room temperature for 1 hour.
[0078] 3) After the reaction is completed, the material is taken out and rinsed with deionized water, and then annealed in air at 250°C for 2 hours to obtain a copper oxide microwire precursor.
[0079] 4) The copper oxide microwire precursor was dissolved in 0.5 M CBS solution at -20 mA·cm -2 The reduction treatment was carried out at a current density of for 2 hours to obtain a copper microwire precursor having a large number of microwire structures.
[0080] 5) Soak the copper microwire precursor in a 2 mM cobalt sulfate solution and let it stand at room temperature for 20 minutes.
[0081] 6) The material was taken out from the cobalt chloride solution, cleaned with deionized water, and dried in an oven at 80°C for 2 hours. Afterwards, it was annealed in a hydrogen atmosphere at 250°C for 2 hours and cooled to room temperature to obtain a cobalt-doped copper microwire catalyst.
[0082] Example 7
[0083] 1) Cut the foam copper into 100×100 cm 2 The samples were ultrasonically cleaned with anhydrous ethanol, 1 M hydrochloric acid and deionized water for 10 min each and dried for later use.
[0084] 2) Immerse the cleaned copper foam in a mixed solution of 0.2 M ammonium persulfate and 3 M sodium hydroxide and let it stand at room temperature for 2 hours.
[0085] 3) After the reaction is completed, the material is taken out and rinsed with deionized water, and then annealed in air at 350°C for 2 hours to obtain a copper oxide microwire precursor.
[0086] 4) The copper oxide microwire precursor was reduced in a 0.5 M PBS solution at -0.4 V vs. RHE for 1 hour to obtain a copper microwire precursor having a large number of microwire structures.
[0087] 5) Soak the copper microwire precursor in a 5 mM nickel chloride solution and let it stand at room temperature for 10 minutes.
[0088] 6) The material was taken out from the cobalt chloride solution, cleaned with deionized water, and dried in an oven at 80°C for 2 hours. Afterwards, it was annealed in a hydrogen atmosphere at 250°C for 2 hours and cooled to room temperature to obtain a nickel-doped copper microwire catalyst.
[0089] Example 8
[0090] 1) Construction of a three-electrode system: The cobalt-doped copper microwire catalyst prepared in Example 1 was installed on an electrochemical workstation as a working electrode, a platinum sheet was used as a counter electrode, a silver-silver chloride electrode was used as a reference electrode, and a 0.5 M PBS aqueous solution was used as the electrolyte. A platinum sheet was used as the counter electrode, and a silver-silver chloride electrode was used as the reference electrode; the area of the catalyst immersed in the electrolyte was 1×1 cm 2 The cathode pool and the anode pool were separated by an ion exchange membrane and stirred by a magnetic pole at a speed of 600 rpm.
[0091] 2) The LSV curve was obtained using the linear scanning method of the electrochemical workstation with a scanning rate of 5 mV / s.
[0092] 3) Add HMF to the 0.5 M PBS aqueous solution to make the concentration reach 100 mM, and obtain the LSV curve at a scan rate of 5 mV / s. The LSV curves obtained in steps 2) and 3) are as follows: Figure 4 As shown in Figure 5, the addition of HMF reduced the onset potential of the electrode, accompanied by an increase in the current density.
[0093] 4) Electrolysis was performed in 5 mL of electrolyte containing 0.5 M PBS aqueous solution and 100 mM HMF using constant potential mode at an electrolysis voltage of -0.5 V vs. RHE.
[0094] Example 9
[0095] 1) Construction of a three-electrode system: The cobalt-doped copper microwire catalyst prepared in Example 2 was installed on an electrochemical workstation as a working electrode, a platinum sheet was used as a counter electrode, a silver-silver chloride electrode was used as a reference electrode, a 0.5 M Na2SO4 aqueous solution was used as the electrolyte, a carbon rod was used as the counter electrode, and a silver-silver chloride electrode was used as the reference electrode; the area of the catalyst immersed in the electrolyte was 1×1 cm 2 The cathode pool and the anode pool were separated by an ion exchange membrane and stirred by a magnetic pole at a speed of 600 rpm.
[0096] 2) The LSV curve was obtained using the linear scanning method of the electrochemical workstation with a scanning rate of 5 mV / s.
[0097] 3) Add 5-hydroxymethyl-2-tetrahydrofuran furfural to the 0.5 M Na2SO4 aqueous solution to make the concentration reach 200 mM, and obtain the LSV curve at the same scanning rate of 5 mV / s.
[0098] 4) Electrolysis was performed in a 10 mL electrolyte solution containing 0.5 M Na2SO4 aqueous solution and 200 mM 5-hydroxymethyl-2-tetrahydrofuran furfural using a constant potential mode at an electrolysis voltage of -0.4 V vs. RHE.
[0099] Example 10
[0100] A three-electrode system was constructed according to the method of Example 8, and HMF was added to the electrolyte to a concentration of 100 mM for electrolysis experiments. The electrolysis potential was -0.5 V vs. RHE. The test results are shown in Figure 5 As shown, when the theoretical charge required for electrolysis is reached, the HMF conversion rate is 96.3% and the BHMF yield is 84.1%. It can be seen that the catalyst prepared by the present invention has high catalytic activity for the HMF electrocatalytic hydrogenation reaction and is highly selective for the reaction path of HMF reduction to BHMF.
[0101] Embodiment 11
[0102] A three-electrode system was constructed according to the method of Example 8. HMF was added to the electrolyte to a concentration of 100 mM for electrolysis experiments. The conversion rate and product of HMF were tested at -0.3, -0.4, -0.5, -0.6, and -0.7 V vs. RHE electrolysis potentials. The results are shown in FIG. Figure 6 The results show that the HMF conversion rate and BHMF yield are optimal at a potential of -0.5 V vs. RHE.
[0103] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a transition metal-doped copper microwire catalyst, characterized in that: The following steps are involved: S1. Prepare copper matrix material, clean and dry it for later use; S2, immersing the pretreated copper substrate material in a mixed solution of ammonium persulfate and sodium hydroxide for ion corrosion; S3, taking out the material from the mixed solution, washing it and performing a first annealing treatment to obtain a copper oxide micron wire precursor; S4, electrochemically reducing the copper oxide microwire precursor to obtain a copper microwire precursor; S5, immersing the copper microwire precursor in a transition metal solution to perform transition metal doping; S6. Taking out the material from the transition metal solution, performing a second annealing treatment after washing, and cooling to room temperature to obtain a transition metal-doped copper microwire catalyst.
2. The method for preparing the transition metal-doped copper microwire catalyst according to claim 1, characterized in that: In step S2, the concentration of ammonium persulfate in the mixed solution is 0.05-0.5 M, the concentration of sodium hydroxide is 0.5-5 M, and the immersion time of the copper matrix material in the mixed solution is 10-120 min.
3. The method for preparing the transition metal-doped copper microwire catalyst according to claim 1, characterized in that: In step S3, the first annealing treatment condition is: annealing at a temperature of 200-350° C. for 0.5-5 h in air or oxygen atmosphere.
4. The method for preparing the transition metal-doped copper microwire catalyst according to claim 1, characterized in that: In step S4, the electrochemical reduction treatment conditions are: in a buffer solution, the reduction treatment is performed at a constant voltage of -0.1 to -0.5 V vs. RHE for 0.5 to 5 h; Alternatively, in buffer, -1 to -100 mA cm -2 The reduction treatment was carried out under constant current for 0.5-5 h; Alternatively, cyclic voltammetry was performed in buffer at a cycling potential of 0 to -0.6 V vs. RHE for 10 to 100 cycles.
5. The method for preparing the transition metal-doped copper microwire catalyst according to claim 1, characterized in that: In the step S5, the concentration of the transition metal solution is 0.1-10 mM, and the immersion time of the copper microwire precursor is 1-30 min.
6. The method for preparing the transition metal-doped copper microwire catalyst according to claim 5, characterized in that: The transition metal element in the transition metal solution is selected from one or more of cobalt, nickel, iron and manganese.
7. The method for preparing a transition metal-doped copper microwire catalyst according to claim 1, characterized in that: In step S6, the second annealing treatment condition is: annealing at a temperature of 200-350° C. for 0.5-5 h in a hydrogen atmosphere.
8. A transition metal-doped copper microwire catalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. A biomass reduction application, characterized in that: The transition metal-doped copper microwire catalyst as described in claim 8 is used for electrocatalytic reduction of furan aldehyde organic small molecules to prepare furanol, and the furan aldehyde organic small molecules are selected from at least one of furfural, 5-hydroxymethylfurfural, 5-formyl-2-furancarboxylic acid, 2,5-diformylfuran, and 5-hydroxymethyl-2-tetrahydrofuran furfural.
10. The biomass reduction application according to claim 9, characterized in that: A three-electrode system was constructed, with the transition metal-doped copper microwire catalyst as the working electrode, the concentration of furan aldehyde organic small molecules was 1~1000 mM, and the reaction potential was -0.1~-1 V vs. RHE.
Citation Information
Cited By
Preparation method and application of Al-doped CuO nanosheet electrocatalyst
CN119824460A